Iḥtijājāt jamāhīrīyah fī al-ḥarakāt al-ijtimāʿīyah: Dirāsat muqāranah bayna aḥdāth ḥadīqat Ghezi al-Turkīyah wa ḥarakat al-difāʿ ʿan al-Islām al-Indūnīsīyah - Ummah, Aniqotul; Perdana, Aditya; Noor, Firman (Studia Islamika, 2024)
This article aims to analyze the motives, goals, and mobilizing actors of the Gezi Park protests in Turkey in 2013 and the Aksi Bela Islam (ABI-Islamic defenders’ action) protests in Indonesia in 2016. The study finds that while both protests have strong Islamic historical roots, their underlying motives are significantly different. The Gezi Park protests were driven by government policies regarding the relocation of the park for commercial purposes, whereas the IDF protests were triggered by a statement made by the former Governor of Jakarta, Basuki Tjahaja Purnama, which was deemed blasphemous to Islam. Both movements share a common mobilizing factor, including the construction of easily understandable narratives for the masses. The ABI amplified public anger by emphasizing the importance of defending Islamic theological values that had been insulted, calling for collective prayer with prominent religious leaders as its key actors. On the other hand, the Gezi Park protests amplified public anger by voicing resistance against state brutality.